The Transformation of German Jewry, 1780-1840. - Sorkin, David Jan (Oxford University Press, 1990)
This treatise argues that the emancipation of German Jews and their subsequent encounter with German culture led not to assimilation, but to the creation of a new Jewish identity and community - a subculture - that produced many of Judaism's modern movements, artists, scientists and academics.